2012
DOI: 10.1016/j.metabol.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of core clock genes in human islets

Abstract: Regulation of core clock genes in human islets.Stamenkovic, Jelena; Olsson, Anders H; Nagorny, Cecilia; Malmgren, Siri; Dekker Nitert, Marloes; Ling, Charlotte; Mulder, Hindrik Link to publication Citation for published version (APA): Stamenkovic, J., Olsson, A. H., Nagorny, C., Malmgren, S., Dekker Nitert, M., Ling, C., & Mulder, H. (2012). Regulation of core clock genes in human islets. Metabolism, Clinical and Experimental, 61(7), 978-985. DOI: 10.1016/j.metabol.2011.11.013 General rights Copyright and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 20 publications
1
57
0
Order By: Relevance
“…This study found that the peak levels of serum concentrations of the markers occurred in the early evening, suggesting a correlation between oxidative damage and increased metabolism. The significance of rhythmic factors in diabetes was also shown in a study that looked at mRNA expression of the core clock genes in cells isolated from patients with and without type 2 diabetes, in addition to insulin secretion (167). The authors found that PER2, PER3, and CRY2 mRNA levels in human islets were significantly lower in patients with type II diabetes than in normal controls.…”
Section: Diabetesmentioning
confidence: 87%
“…This study found that the peak levels of serum concentrations of the markers occurred in the early evening, suggesting a correlation between oxidative damage and increased metabolism. The significance of rhythmic factors in diabetes was also shown in a study that looked at mRNA expression of the core clock genes in cells isolated from patients with and without type 2 diabetes, in addition to insulin secretion (167). The authors found that PER2, PER3, and CRY2 mRNA levels in human islets were significantly lower in patients with type II diabetes than in normal controls.…”
Section: Diabetesmentioning
confidence: 87%
“…The MTNR1B variant is an established locus associated with type 2 diabetes, and variants at CRY2 have been tentatively associated with type 2 diabetes [6]. In human islets, the expression of CRY2 mRNA has been shown to be negatively correlated with levels of glycated haemoglobin, and the expression of CRY2 mRNA was lower in participants with type 2 diabetes [7]. Several recently published studies have further indicated the importance of CRY2 and its circadian co-regulator CRY1 on glucose metabolism and energy homeostasis in mice [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that clock gene expression is impaired in individuals with metabolic syndrome, and, further, that impairments in transcript levels of PER3 in human leukocytes occur in diabetic subjects and gestational diabetic women [33,34]. Interestingly, mRNA of PER3 has been found to be inversely proportional to the glycated hemoglobin levels in T2DM patients [31,34]. Taken together, these findings suggest that impaired Per3 may influence glucose metabolism.…”
Section: Discussionmentioning
confidence: 88%